Directed differentiation of human induced pluripotent stem cells into functional cholangiocyte-like cells - Sampaziotis, Fotios; de Brito, Miguel Cardoso; Geti, Imbisaat; Bertero, Alessandro; Hannan, Nicholas R.F.; Vallier, Ludovic (Nature Publishing Group, 2017)
The difficulty in isolating and propagating functional primary cholangiocytes is a major limitation in the study of biliary disorders and the testing of novel therapeutic agents. To overcome this problem, we have developed a platform for the differentiation of human pluripotent stem cells (hPSCs) into functional cholangiocyte-like cells (CLCs). We have previously reported that our 26-d protocol closely recapitulates key stages of biliary development, starting with the differentiation of hPSCs into endoderm and subsequently into foregut progenitor (FP) cells, followed by the generation of hepatoblasts (HBs), cholangiocyte progenitors (CPs) expressing early biliary markers and mature CLCs displaying cholangiocyte functionality. Compared with alternative protocols for biliary differentiation of hPSCs, our system does not require coculture with other cell types and relies on chemically defined conditions up to and including the generation of CPs. A complex extracellular matrix is used for the maturation of CLCs; therefore, experience in hPSC culture and 3D organoid systems may be necessary for optimal results. Finally, the capacity of our platform for generating large amounts of disease-specific functional cholangiocytes will have broad applications for cholangiopathies, in disease modeling and for screening of therapeutic compounds.